Tokyo commute Japanese customs and way of life viewed from the Odakyū Line - Lee, A. Robert 1941- (Renaissance Books, 2011)
A unique take on modern life in Tokyo, Japan's capital city. A Japan of trains, everyday to and fro, carriage scenes and theatre, vistas from the window, advertising posters. Each to be savoured through a specific Tokyo line - the Odakyu. Pitched as creative text and colour illustrations, 'Tokyo Commute' offers on-track and off-track observations. A gallery of mirrors, musings, memories. This is less documentary than iconography, a poetics of Japanese routine and etiquette. It offers a wry diary of month-and-weekday observations, a 'map' of Shinjuku as key station and gathering place, a run of notable Tokyo locations - from the national bunraku theatre to a Kawasaki sludge recycling centre. Other Odakyu travel involves the Hakone open air art gallery, Narita as both airport and temple-complex, Yokohama as history and Chinatown. Essential reading for first-time, and second-time, visitors, and even regular commuters